Effect of Antibiotics and Gelling Agents in Transformation of Brinjal (Solanum melongena L.) cv. Manjarigota - D P Prakash (Society for Promotion of Horticulture - Indian Institute of Horticultural Research, 2007)
A study was conducted to find out the effect of antibiotics and gelling agents on Agrobacterium-mediated transformation using hypocotyl explants of brinjal cv. Manjarigota. Hypocotyl explants of brinjal were found to be sensitive even to the lowest level of kanamycin (25 mg/l) tested. Explants that showed increased callus initiation and regeneration response upon cocultivation with Agrobacterium and on kanamycin at 100 mg/l were selected as this indicated a highly effective selection pressure. Cefotaxime did not affect regeneration response and at 500 mg/l, it effectively inhibited Agrobacterium overgrowth completely on Agrobacterium cocultivated hypocotyl explants. There were marked differences in regeneration response in hypocotyl explants cultured on medium solidified with various gelling agents indicating the influence of gelling agent on the activity of kanamycin in culture medium, which indirectly affects selection and recovery of transformants. Antibiotics and gelling agents could therefore affect, directly or indirectly, transformation of brinjal cv. Manjarigota.